The Effect of Major Surgical Procedures on Plasma and Platelet Levels of Factor XIII - Letheby, Beth A; Davis, Richard B; Larsen, Arden E (Thrombosis and Haemostasis, 1974)
Factor XIII (FSF or fibrinoligase), an enzyme required for normal blood coagulation, can be measured by its catalysis of the incorporation of a fluorescent amine, monodansylcadaverine (N-(5-aminopentyl)-5-dimethylamino-l-naphthalene-sulfon-amide) into casein. The amine incorporation test was applied to fourteen patients who had major operations. Levels of factor XIII were measured before surgery and at intervals of two, four, and six days after operation. Plasma factor XIII showed a significant, linear decrease for each day after surgery. Patients having orthopedic surgery showed less pronounced changes than the remaining patients. Factor XIII also decreased after operation in patients with neoplastic disease, but the change was not different from that after general surgical procedures done in the absence of neoplasia. Platelet factor XIII levels were increased on the second day after operation, diminished on day four, and increased above pre-operative levels on the sixth day after surgery. Possible explanations of the observations are presented.